USE OF JAPANESE EXPERIENCE IN EFFECTIVE MANAGEMENT OF EMPLOYEES IN ENTERPRISES AND ORGANIZATIONS - Rakhmatullaeva Nargiza Oktyabrevna (Galaxy International Interdisciplinary Research Journal, 2022)
The article examines the effective management of employees in enterprises and organizations and the effective use of Japanese experience in this process.